Hydrostatic reduction of intussusception under ultrasound guidance: an initial experience in a developing country (2007)
Background: Intussusception is one of the most common causes of acute intestinal obstruction in children. Hydrostatic reduction with barium enema is the widely accepted and preferred mode of treatment of uncomplicated intussuception. The aim of this study was to report our initial experience with hydrostatic reduction of intussusception. Patients and methods: We present our initial experience in which 8 patients had ultrasound guided hydrostatic reduction of intussusception over a period of 2 years. All patients that presented within 48hours of onset of symptoms were recruited into the study. Clinical diagnosis of intussusceptions was made in all of them while abdominal ultrasound was used to confirm the diagnosis. Results: Half of the patients presented after 24 hours of onset of symptoms. Five patients (62.5%) had a successful reduction of thier instussusception while was completed by surgery. There was only one (12.5%) recurrence and there was no peritonitis. Conclusion: Ultrasound guided hydrostatic reduction of intussusceptions in this environment is possible when patients present early with low risk of complication and low recurrence rate.